MEMBANGUN KESADARAN MORAL DALAM ETIKA BERINTERAKSI DI DUNIA MAYA - Rachmat Adi Purnama (Cakrawala - Jurnal Humaniora, 2009)
Level of crime has had with the empirical branching directly or through cyber space or virtual world. Based on the data showed that a variety of behavioral changes and the more crime increase with the virtual world of crime. Meanwhile the government and the device has not been able to become legal issues existing controllers. ITE legislation which was passed in last March 2008 full debate is considered not healthy and in conflict with the Constitution, especially on the freedom of UUD 45. By using qualitative methods, the author tried to analyze and give a solution that may become a concern for the government and the public how to maintain ethics in the virtual world interacting with the moral awareness of how to build each individual IT users themselves.Keywords: crime, ethics, the moral awareness